Milk fatty acid profile from grazing buffaloes fed a blend of soybean and linseed oils - Gagliostro, Gerardo Antonio; Patiño, Exequiel Maria; Sánchez Negrete, María Gabriela; Sager, Gerardo Enrique; Castelli, Laura; Antonacci, Liliana; Raco, Fernando; Gallello, Lucas; Rodriguez, M.A.; Cañameras, Carlos; Zampatti, Mariela; Bernal, Claudio Adrián (Escola de Veterinária, Universidade Federal de Minas Gerais, 2019)
The aim of the study was to examine the changes in milk fatty acid (FA) profile of grazing buffaloes fed either low (L, 276g/d) or high (H, 572g/d) doses of a blend (70:30, wt/wt) of soybean and linseed oils. Fourteen multiparous Mediterranean buffaloes grazing on a native pasture were fed 4 kg/day of a commercial concentrate containing no supplemental oil over a pre-experimental period of ten days. The baseline milk production and composition and milk FA profile were measured over the last three days. After this pre-experimental period the animals received the same concentrate added with either the L or H oil doses for 26 additional days. Milk yield (g/animal/day) did not differ at the start (1776 ± 522 and 1662 ± 291 for L and H, respectively, P<0.622) or at the end of the trial (4590 ± 991 and 4847 ± 447 in L and H, respectively, P<0.543). Baseline milk fat content (g/kg) averaged 77.1 (±20.5) in L and 74.3 (±9.9) in H (P<0.10) and was reduced (P<0.031) to 60.7 (±23.6) and 49.4 (±11.2) (P<0.0031) respectively after L and H with no differences between treatments (P<0.277). Baseline milk protein content (L=43.2 ± 3.4 and H= 44.3 ± 6.9g/kg) increased after oil supplementation (P<0.0001) in both L (73.2 ± 6.0g/kg) and H (68.4 ± 4.9g/kg) without differences between oil doses (P<0.123). Milk fat content of 14:0 decreased after oil supplementation only in the H treatment (5.29 to 4.03, P<0.007) whereas that of 16:0 was reduced (P<0.001) at both L (24.49 to 19.75g/100g FA) and H (25.92 to 19.17g/100g FA) doses. The reduction of total content of 12:0 to 16:0 was higher (P<0.052) in H (32.02 to 23.93g/100g FA) than L (30.17 to 25.45g/100g FA). Vaccenic acid content increased (P<0.001) from 5.70 to 13.24g/100g FA in L and from 5.25 to 16.77 in H, with higher results in the in H treatment (P<0.001). Baseline rumenic acid was sharply increased (P<0.001) in L (1.80 to 4.09g/100g FA, +127%) and H (1.60 to 4.61g/100g FA, +187%) with no differences between L and H (P<0.19). Overall, these results indicate a pronounced improvement in the nutritional value of milk fat from grazing buffaloes fed little amounts (0.276g/day) of a blend of soybean and linseed oils.